(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Craniofacial anthropometry is an important stem of anthropometry, in which the dimensions of the head and face are measured. It provides quantitative data, identifying people having different physical characteristics, diagnosing people having craniofacial abnormality related to congenital or genetic cause and differentiating between males and females. Objective: The purpose of the present study was to establish the ethnic anthropometric data for adult tribal (Garo) and non-tribal Bangladeshi female. Methodology: This cross sectional analytical type of study was conducted in Department of Anatomy, Sir Salimullah Medical College, Dhaka, from January 2015 to December 2015.The study materials consist of two hundred (200) adult Bangladeshi female of greater Mymensingh district age ranging from 25 to 45 years. Results: Among 200 female, 100 was tribal (Garo) female and 100 non-tribal female, the mean (±SD) facial height from ‘nasion to gnathion’ was higher in non-tribal female than tribal female (p<0.001). Conclusion: Facial height from ‘nasion to gnathion is higher in non-tribal female compared to tribal female among Bangladeshi female living in Mymensingh district. Journal of Current and Advance Medical Research 2020;7(1): 36-39